Membrane filtration of microalgae - Nurulhuda Abdul Rahim. (2011)
Extracellular polymeric substances (EPS) are known to greatly affect membrane fouling. This holds true for microalgal EPS. Previous literatures have reported on the worsening effect of higher EPS concentration on microalgae fouling during microfiltration and ultrafiltration. However, no previous study examined which fraction of EPS was the main contributor to fouling. The purpose of this study was thus to investigate the role of bound EPS (B-EPS). This was carried out by comparing the fouling observed for whole cell filtrations against the fouling observed for filtrations of B-EPS. B-EPS was extracted from 50mg/L algae suspension using the cation exchange resin method with an extraction time of 6 hours. 20, 50 and 100 mg/L whole cell filtrations were carried out at fluxes of 15, 20, 25, 30, 35 and 40 LMH while 50mg/L B-EPS filtrations were carried out at fluxes of 15 and 20 LMH. It was determined that the TMP increase of B-EPS was 97.7% of the TMP increase of whole cells for 15LMH and 99.8% of the TMP increase of whole cells for 20LMH. This suggests that B-EPS fouling is a major contributor in whole cell fouling. Optical density results showed that B-EPS had higher recovery rates as compared whole cells. This suggests that the B-EPS fragments were easily transported and deposited onto the membrane surface than whole cells, likely due to their smaller size and adhesive properties. More studies need to be done to ascertain to what extent these two characteristics of B-EPS, as well as other characteristics, affect its fouling potential and influence its role in whole cell fouling.